Los simuladores de negocios como alternativa del desarrollo de las competencias de los estudiantes de la Universidad Técnica de Cotopaxi, de la carrera de ingeniería comercial, periodo 2013, 2014 - Villegas Collantes, Jenny del Rocío (2015)
This research was conducted in order to develop a teaching guide Business Simulation Game Simul @ will help meet critical aspects of creating and managing a business project in the students of the Technical University of Cotopaxi Career Commercial Engineering This project will provide students with access to new technologies generating common situations that entrepreneurs and business day in order to contribute to their academic process face….